Selective synthesis of N-unsubstituted and N-arylindoles by the reaction of arynes with azirines - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; "Jain, Shailja"; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2016)
The transition-metal-free and temperature-dependent highly selective reaction of arynes with 2H-azirines allowing the synthesis of either N-unsubstituted or N-arylindoles has been developed. At 60 degrees C, arynes generated from 2-(trimethylsilyl)aryl triflates smoothly insert into 2H-azirines to form 2,3-diarylindoles with high selectivity. Interestingly, when the reaction was performed at -10 degrees C, the selectivity was switched to the formation of 1,2,3-triarylindoles in good yields.

Substrate-controlled selectivity switch in the three-component coupling involving arynes, aromatic tertiary amines, and CO2 - Bhojgude, Sachin Suresh; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
The transition-metal-free multicomponent coupling involving arynes, aromatic tertiary amines, and CO2 is reported. The reaction exhibits switchable selectivity depending on the electronic nature of the aromatic amines used. With amines bearing electron-releasing/neutral groups as the nucleophilic trigger, the reaction afforded 2-arylamino benzoates via a nitrogen to oxygen alkyl group migration. Employing electron-deficient amines in the reaction furnished 2-aminoaryl benzoates proceeding via the aryl to aryl amino group migration resembling a Smiles rearrangement.